Early remission status predicts long-term outcomes in patients with Crohn's disease treated with certolizumab pegol. (1st December 2016) - Melmed, Gil Y.; McGovern, Dermot; Schreiber, Stefan; Kosutic, Gordana; Spearman, Marshall; Coarse, Jason; Sandborn, William J.
Abstract: Background: In Crohn's disease (CD), rapid response to anti–tumor necrosis factor therapy improves short- and medium-term outcomes, but the relationship between early remission (ER) and long-term remission is unclear. Aims: This exploratory analysis of PRECiSE 3 (NCT00160524) assessed whether ER after initiation of certolizumab pegol predicted long-term remission. Methods: Patients enrolled in PRECiSE 3 had completed PRECiSE 1 or 2, two randomized placebo-controlled studies for moderate to severe CD, and received open-label certolizumab pegol 400 mg every 4 weeks for a total treatment duration of ≤7.5 years. Time to loss of remission between patients with and without ER (Harvey–Bradshaw Index ≤4 at or before Week 6 of PRECiSE 1 or 2) was compared by log-rank test of Kaplan–Meier estimates. Results: At baseline, patients with ( n  = 242) and without ( n  = 148) ER had mean (standard deviation [SD]) durations of CD of 6.8 (6.6) and 7.4 (7.8) years, mean (SD) CD Activity Index scores of 280.3 (53.4) and 311.1 (55.5), with 45.5% and 41.9% of patients having ileocolonic CD, and median C-reactive protein concentrations of 8.0 and 5.0 mg/L, respectively. Median certolizumab pegol plasma concentrations during the first 6 weeks of therapy were similar in both groups. Mean time to loss of remission was significantly longer in patients with versus without ER (2.77 vs. 1.14 years, p  < 0.0001). Conclusions: In certolizumab pegol–treated patients with CD, ER appears to be an important predictor of long-term clinical remission. Prospective trials are needed to determine whether ER improves other long-term outcomes.